Post-exposure prophylaxis (PEP) for rabies with purified chick embryo cell vaccine: a systematic literature review and meta-analysis - Scott Preiss; Pornthep Chanthavanich; Lin H. Chen; Cinzia Marano; Philippe Buchy; Rosa van Hoorn; Marije Vonk Noordegraaf; Piyali Mukherjee (Taylor & Francis Group, 2018)
Introduction: Fifteen million people each year receive post-exposure prophylaxis (PEP) to prevent rabies, yet the disease remains neglected and highly under-reported. Areas covered: In this systematic literature review, we assessed the immunogenicity, efficacy, and safety of a purified chick embryo cell-culture rabies vaccine (PCECV) for PEP against rabies by intramuscular (IM) or intradermal (ID) administration. We performed meta-analyses to compare immunogenicity according to the route of vaccine administration, study population, and PEP regimen, such as number of doses, and concomitant rabies immunoglobulin. Expert commentary: There were 54 estimates of immune responses to vaccination, which showed that in the overall population, after starting PEP with PCECV by the IM or ID route (≥2.5 IU per dose), almost all individuals had rabies virus neutralizing antibody (RVNA) titers above the World Health Organization (WHO) recommended serological threshold for an adequate immune response to vaccination (RVNA ≥0.5 IU/ml by day 14). In the overall population, PCECV had an acceptable safety profile. However, given that there are 59,000 human rabies deaths reported annually, the challenge is to improve access to PCECV for PEP against human rabies.